1990
DOI: 10.1007/bf00194222
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of specific sequences or modification of centromeric chromatin are responsible for Y chromosome centromere inactivation

Abstract: Stable dicentric chromosomes behave as monocentrics because one of the centromeres is inactive. The cause of centromere inactivation is unknown; changes in centromere chromatin conformation and loss of centromeric DNA elements have been proposed as possible mechanisms. We studied the phenomenon of inactivation in two Y centromeres, having as a control genetically identical active Y centromeres. The two cases have the following karyotypes: 45, X/46,X,i(Y)(q12) and 46,XY/47,XY,+t(X;Y) (p22.3;p11.3). The analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…In addition, the proper folding of chromosomal DNA through the eentromere into a higher order chromatin structure is a prerequisite for a subunit repeat model proposed for the mammalian centromere-kinetochore complex (Zinkowski et al, 1991). It has also been reported that modification of the chromatin of one centromere on a dicentric Y chromosome leads to inactivation of this centromere (Maraschio et al, 1990), further supporting the idea that correct chromatin organization is essential for centromere function.…”
mentioning
confidence: 68%
“…In addition, the proper folding of chromosomal DNA through the eentromere into a higher order chromatin structure is a prerequisite for a subunit repeat model proposed for the mammalian centromere-kinetochore complex (Zinkowski et al, 1991). It has also been reported that modification of the chromatin of one centromere on a dicentric Y chromosome leads to inactivation of this centromere (Maraschio et al, 1990), further supporting the idea that correct chromatin organization is essential for centromere function.…”
mentioning
confidence: 68%
“…Moreover, this term was earlier used to describe mosaic ring chromosome losses and gains (McDermott et al, 1977). Finally, previous observations have shown alterations to chromosome Y structure underlying the loss during mitotic cell division and, consequently, mosaicism formation (Haaf and Schmid, 1990;Maraschio et al, 1990;Hsu, 1994). Therefore, dynamic mosaicism is an appropriate term to describe intercellular karyotype variability in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Copyright © 2008 S. Karger AG, Basel Chromosomal mosaicism is a consistent finding in cases of isodicentric Y chromosomes, which represent the most commonly-reported structural abnormality of the Y chromosome (Hsu, 1994;DesGroseilliers et al, 2006). This is usually attributed to the instability of rearranged Y chromosomes during cell division associated with centromere inactivation (Therman et al, 1986;Haaf and Schmid, 1990;Maraschio et al, 1990). As a result, a 45,X cell line coupled This work was partially supported by Philip Morris USA, Inc.…”
mentioning
confidence: 99%
“…those lacking a primary constriction at mitosis, can be found in dicentric chromosomes, which thus evade the breakage-fusion-bridge cycle (McClintock 1938). Rearrangements of the DNA have been detected at a small proportion of such inactive centromeres, including large cytogenetically visible deletions (Vianna-Morgante and Rosenberg 1986) and smaller deletions detectable by in situ hybridisation (Maraschio et al 1990) or molecular analysis . However, no change to the DNA could be detected at most inactive centromeres (TylerSmith et al 1993).…”
Section: Introductionmentioning
confidence: 98%